Production method of recovered fine aggregate for concrete and production method of ready-mixed concrete

By treating recovered fine aggregate with microbubble water, iron oxide, and cationic surfactants, the method effectively removes cement content, addressing quality issues and producing high-quality aggregate for superior ready-mixed concrete.

JP2024176696AActive Publication Date: 2024-12-19IZUMI READY MIXED CONCRETE PLANT
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023095441
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2024-12-19
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

Existing methods fail to produce high-quality recovered fine aggregate for concrete due to high water absorption and cement content, leading to quality deterioration and operational issues in ready-mixed concrete production.

Method used

A method involving the use of microbubble water and iron oxide, followed by a cationic surfactant and percarbonate treatment, to effectively remove cement content from recovered fine aggregate, enhancing its quality.

Benefits of technology

The method produces high-quality recovered fine aggregate with reduced water absorption and cement content, enabling the production of superior ready-mixed concrete with improved stability and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176696000001
    Figure 2024176696000001
Patent Text Reader

Abstract

To provide a production method of a recovered fine aggregate for concrete capable of producing high-quality recovered fine aggregate for concrete.SOLUTION: A production method of a recovered fine aggregate for concrete comprises the steps of: adding a first treating agent having microbubble water and iron oxide to a derivative of returned ready-mixed concrete or residual concrete; and adding a second treating agent having a cationic surfactant to the derivative to which the first treating agent has been added.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing recycled fine aggregate for concrete, and a method for producing ready-mix concrete. [Background technology]

[0002] Even if the ready-mixed concrete produced at a factory (ready-mixed concrete factory) that produces ready-mixed concrete is delivered to a construction site by an agitator truck, if there is any left over at the construction site, it is returned to the ready-mixed concrete factory while still loaded on the agitator truck. Such unused ready-mixed concrete is called returned ready-mixed concrete and leftover ready-mixed concrete, and fine aggregate may be recovered from such unused ready-mixed concrete. Such recovered fine aggregate is called recovered fine aggregate and recovered sand, but the quality may not be high enough to be used as fine aggregate for the production of ready-mixed concrete. In such a case, the fine aggregate recovered from the returned ready-mixed concrete or leftover ready-mixed concrete may be discarded. In addition, the returned ready-mixed concrete and leftover ready-mixed concrete may be discarded as it is. However, for the purpose of effective reuse of resources and reduction of waste volume, etc., a method for producing recovered fine aggregate that can be suitably used as fine aggregate for concrete from the returned ready-mixed concrete or leftover ready-mixed concrete is required.

[0003] Examples of methods for producing recycled fine aggregate for concrete include the method described in Patent Document 1. Patent Document 1 describes a method for producing aggregate from returned concrete, which includes the steps of: charging the returned concrete into a high-power mixer; adding an organic or inorganic coagulant mixture, either alone or in combination; mixing the returned concrete for 20 seconds to 5 minutes until the returned concrete solidifies and becomes substantially dry, does not contain cement paste, and has a larger particle size fraction consisting mainly of the original natural aggregate contained in the returned concrete, and a smaller particle size fraction consisting mainly of agglomerates containing water, coagulant mixture, fresh cement, and fine fractions of the mixture (sand and silt); and separating the mixture by vibrating, rotating, or passing it through a cyclone sieve to separate it into at least two particle size classes, one of which is a larger particle size fraction consisting mainly of the original natural aggregate contained in the returned concrete that is substantially dry and does not contain cement paste, and one of which is a smaller particle size fraction consisting mainly of agglomerates containing water, coagulant mixture, fresh cement, and fine fractions of the mixture (sand and silt). According to US Pat. No. 5,399,436, aggregates can be produced from concrete residues not used for construction purposes or, more generally, from cement mixtures that are not used for any reason and are returned to the production facility in the mixer truck. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2020-528858 Summary of the Invention [Problem to be solved by the invention]

[0005] As mentioned above, fine aggregate recovered from returned ready-mix concrete or residual ready-mix concrete, etc. (recovered fine aggregate) may not be of sufficiently high quality to be used in the production of ready-mix concrete. Specifically, such recovered fine aggregate tends to have a high water absorption rate of the aggregate itself compared to ordinary aggregate, and may be of low quality as fine aggregate for concrete. In addition, when such fine aggregate for concrete is stored in a silo or the like, it tends to easily solidify. This affects the operating conditions, etc., when the recovered fine aggregate for concrete is used to produce ready-mix concrete. In addition, recovered fine aggregate tends to be more susceptible to quality deterioration than recovered coarse aggregate.

[0006] For these reasons, fine aggregates recovered from returned ready-mixed concrete or residual ready-mixed concrete, such as recovered aggregates specified in JIS A 5308:2019, and recycled aggregates, exist, but there are recovered fine aggregates of higher quality than, for example, recycled aggregates for concrete H and recycled aggregates for concrete M. The recycled aggregates for concrete H are specified in JIS A 5021:2018, and are recycled aggregates for concrete produced by subjecting concrete blocks generated by the demolition of structures, etc., to advanced processing such as crushing, grinding, and classification. The recycled aggregates for concrete M are specified in JIS A 5022:2018, and can be handled in a manner similar to ordinary aggregates, and are high-quality aggregates that can be used regardless of the part of the building.

[0007] Even if fine aggregate is recovered from returned ready concrete or residual ready concrete, it is required to obtain a recycled fine aggregate for concrete of the level of recycled aggregate for concrete H or recycled aggregate for concrete M. However, a method for obtaining a sufficiently high-quality recycled fine aggregate for concrete from returned ready concrete or residual ready concrete has not been established. Specifically, for example, even with the method described in Patent Document 1, there are cases where the problem of the remaining cement content (cement paste) contained in the returned concrete in the aggregate obtained from the returned concrete (recovered aggregate) is not fully solved. In particular, among the recovered aggregates, it is more difficult to remove the cement content from the recovered fine aggregate than when producing recovered coarse aggregate, and it is more difficult to obtain a high-quality recovered fine aggregate. For this reason, a manufacturing method for obtaining a high-quality recycled fine aggregate for concrete is required.

[0008] The present invention has been made in consideration of the above circumstances, and has an object to provide a method for producing recycled fine aggregate for concrete, which is capable of producing high-quality recycled fine aggregate for concrete. Another object of the present invention is to provide a method for producing ready-mixed concrete, which is capable of producing high-quality ready-mixed concrete. [Means for solving the problem]

[0009] As a result of various investigations, the present inventors have found that the above object can be achieved by the present invention described below.

[0010] A method for producing recycled fine aggregate for concrete according to a first aspect of the present invention includes the steps of adding a first treatment agent containing microbubble water and iron oxide to a product derived from returned ready-mixed concrete or residual ready-mixed concrete, and adding a second treatment agent containing a cationic surfactant to the product to which the first treatment agent has been added.

[0011] According to this configuration, it is possible to provide a manufacturing method for recycled fine aggregate for concrete, which can produce high-quality recycled fine aggregate for concrete.

[0012] In the conventional manufacturing method of recycled fine aggregate, the recycled fine aggregate has a tendency to have high water absorption of the aggregate itself, and the quality of the recycled fine aggregate as a fine aggregate for concrete could not be sufficiently improved. This is considered to be due to the fact that, when the fine aggregate is recovered from the returned fresh concrete and the remaining fresh concrete, the cement content (cement paste) derived from the returned fresh concrete and the remaining fresh concrete is not sufficiently removed from the fine aggregate, and the cement content remains in the fine aggregate. In contrast, the manufacturing method of recycled fine aggregate for concrete according to the first aspect of the present invention can manufacture a high-quality recycled fine aggregate for concrete. In the manufacturing method of recycled fine aggregate for concrete according to the first aspect of the present invention, a first treatment agent containing microbubble water and iron oxide is added to a product derived from the returned fresh concrete or the remaining fresh concrete, and then a second treatment agent containing a cationic surfactant is added. It is considered that the cement content is suitably removed from the fine aggregate contained in the product. Therefore, it is considered that a high-quality recycled fine aggregate for concrete can be manufactured. Specifically, it is considered that the cement component attached to the fine aggregate contained in the derived product (for example, cement component of cement paste derived from returned fresh concrete and residual fresh concrete) is easily swollen by the first treatment agent. Even when returned fresh concrete and residual fresh concrete themselves are used as the derived product, it is considered that the cement component attached to the fine aggregate contained in the returned fresh concrete and residual fresh concrete is easily swollen. It is considered that the swelling of the cement component makes the cement component easily peeled off from the fine aggregate contained in the derived product that becomes the fine aggregate for concrete. Then, it is considered that the cement component in this easily peeled state is suitably peeled off and removed from the fine aggregate contained in the derived product that becomes the fine aggregate for concrete by the second treatment agent. Therefore, it is considered that the manufacturing method for recycled fine aggregate for concrete according to the first aspect of the present invention can obtain high-quality recycled fine aggregate for concrete from which the cement component is suitably removed.

[0013] A second aspect of the present invention relates to a method for producing recycled fine aggregate for concrete, which is the method for producing recycled fine aggregate for concrete according to the first aspect of the present invention, further comprising a step of adding a third treatment agent containing percarbonate to the derived material to which the second treatment agent has been added.

[0014] According to this configuration, a higher quality recycled fine aggregate for concrete can be obtained. This is believed to be because the third treatment agent more effectively removes the cement content from the fine aggregate contained in the derived material to be used as the fine aggregate for concrete.

[0015] A third aspect of the present invention relates to a method for producing recycled fine aggregate for concrete, which is the method for producing recycled fine aggregate for concrete according to the first aspect of the present invention, further comprising a step of spraying microbubble water onto the derived material to which the second treatment agent has been added, or a step of immersing the derived material to which the second treatment agent has been added in microbubble water.

[0016] According to this configuration, a higher quality recycled fine aggregate for concrete can be obtained. This is believed to be because, by spraying or immersing the microbubble water, the cement content is more effectively removed from the fine aggregate contained in the derived material to be used as the fine aggregate for concrete, and the cationic surfactant that may remain in the fine aggregate is also more effectively removed.

[0017] A fourth aspect of the present invention is a method for producing recycled fine aggregate for concrete, which is the method for producing recycled fine aggregate for concrete according to the second aspect of the present invention, further comprising a step of spraying microbubble water onto the derived material to which the third treatment agent has been added, or a step of immersing the derived material to which the third treatment agent has been added in microbubble water.

[0018] According to this configuration, a higher quality recycled fine aggregate for concrete can be obtained. This is believed to be because, by spraying or immersing in the microbubble water, the cement content is more effectively removed from the fine aggregate contained in the derived material to be used as the fine aggregate for concrete, and the cationic surfactant and the percarbonate that may remain in the fine aggregate are also more effectively removed.

[0019] A method for producing ready-mix concrete according to a fifth aspect of the present invention includes a step of mixing cement, aggregate, and water, and uses, as the aggregate, aggregate containing recycled fine aggregate for concrete produced by the method for producing recycled fine aggregate for concrete according to any one of the first to fourth aspects of the present invention.

[0020] According to this configuration, it is possible to provide a method for producing ready-mixed concrete that can produce high-quality ready-mixed concrete. Specifically, by using as aggregate an aggregate containing recycled fine aggregate for concrete produced by the method for producing recycled fine aggregate for concrete according to any one of the first to fourth aspects of the present invention, it is possible to produce high-quality ready-mixed concrete. Effect of the Invention

[0021] According to the present invention, it is possible to provide a method for producing recycled fine aggregate for concrete, which is capable of producing high-quality recycled fine aggregate for concrete. Also, according to the present invention, it is possible to provide a method for producing ready-mixed concrete, which is capable of producing high-quality ready-mixed concrete. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these.

[0023] A method for producing recycled fine aggregate for concrete according to one embodiment of the present invention includes a step of adding a first treatment agent containing microbubble water and iron oxide to a material derived from returned ready-mixed concrete or residual ready-mixed concrete (first adding step), and a step of adding a second treatment agent containing a cationic surfactant to the material to which the first treatment agent has been added (second adding step).

[0024] The derived material is not particularly limited as long as it is derived from returned ready mixed concrete or from residual ready mixed concrete. The returned ready mixed concrete and the residual ready mixed concrete are ready mixed concrete produced at a ready mixed concrete plant or the like that is transported to a construction site by an agitator truck or the like, but is returned to the ready mixed concrete plant. Among these, the returned ready mixed concrete is ready mixed concrete that is not used at a construction site or the like, but is returned as it is to the ready mixed concrete plant. The residual ready mixed concrete is ready mixed concrete that remains in an agitator truck or the like that has returned from a construction site or the like.

[0025] The derived material may be, for example, the returned fresh concrete or the remaining fresh concrete. That is, in this case, the manufacturing method is a manufacturing method for recycled fine aggregate for concrete, which includes a step of adding a first treatment agent containing microbubble water and iron oxide to the returned fresh concrete or the remaining fresh concrete, and a step of adding a second treatment agent containing a cationic surfactant to the returned fresh concrete or the remaining fresh concrete to which the first treatment agent has been added. Whether the derived material is the returned fresh concrete or the remaining fresh concrete, the manufacturing method can manufacture a high-quality recycled aggregate for concrete. In addition, examples of the derived material include the returned fresh concrete diluted with water such as microbubble water, the remaining fresh concrete diluted with water such as microbubble water, fine aggregate extracted from the returned fresh concrete, and fine aggregate extracted from the remaining fresh concrete. Specifically, the fine aggregate may be a fine aggregate extracted from the returned ready concrete to which water has been added, by adding water such as microbubble water to the returned ready concrete, or a fine aggregate extracted from the remaining ready concrete to which water has been added, by adding water such as microbubble water to the remaining ready concrete. When microbubble water is used for the fine aggregate extracted from the returned ready concrete or the remaining ready concrete, the manufacturing method includes a step of adding microbubble water to the returned ready concrete or the remaining ready concrete, a step of extracting fine aggregate from the returned ready concrete or the remaining ready concrete to which the microbubble water has been added, a step of adding a first treatment agent containing microbubble water and iron oxide to the fine aggregate, and a step of adding a second treatment agent containing a cationic surfactant to the fine aggregate to which the first treatment agent has been added. Whether the derived material is an aggregate extracted from the returned ready concrete or a fine aggregate extracted from the remaining ready concrete, the manufacturing method can produce a high-quality recovered aggregate for concrete.

[0026] In the first addition step, a first treatment agent containing microbubble water and iron oxide is added to the derived material.

[0027] The first treatment agent is not particularly limited as long as it is a treatment agent containing microbubble water and iron oxide, and examples thereof include a treatment agent (dispersion liquid) in which iron oxide is dispersed in microbubble water. Examples of the first treatment agent include a liquid obtained by immersing an iron-containing object (iron-containing material) in microbubble water. It is considered that this liquid becomes a treatment agent in which iron oxide is dispersed in microbubble water by immersing the iron-containing object in microbubble water, whereby iron present near the surface of the iron-containing object is oxidized, and the iron oxide is separated from the iron-containing object. The iron-containing object is not particularly limited as long as iron is present near its surface, and may be made of iron, for example. Examples of the iron-containing object that is the raw material for the iron oxide include iron nails and iron in disposable hand warmers. Examples of the iron in the disposable hand warmers include iron-containing objects in used disposable hand warmers. The conditions for preparing the first treatment agent are not particularly limited as long as the first treatment agent can be obtained. For example, the time for immersing the iron-containing material in the microbubble water is preferably 5 minutes to 60 hours, and more preferably 30 minutes to 60 hours. The temperature of the microbubble water in which the iron-containing material is immersed is not particularly limited. For example, it is preferably 5 to 50°C, more preferably 5 to 40°C, even more preferably 10 to 40°C, and particularly preferably 10 to 35°C, and may be, for example, room temperature. The amount of the microbubble water added is preferably 10 to 10,000 parts by mass, and more preferably 50 to 1,000 parts by mass, relative to 100 parts by mass of the iron-containing material. When the iron-containing material is immersed in the microbubble water, the microbubble water may be subjected to a bubbling treatment. The first treatment agent may be, for example, a liquid or semi-solid state. The liquid state may be, for example, a paste state. The semi-solid state is classified as a state of 30 Pa·s or more in the JAS standard, and examples of such a state include a state of 30 Pa·s or more.

[0028] The microbubble water is water containing microbubbles, and examples of the microbubble water include those specified in ISO 20480-1:2017. The average particle size of the microbubbles is preferably 0.1 to 100 μm, and more preferably 0.1 to 50 μm. Examples of the average particle size of the microbubbles include a volume-equivalent sphere diameter, such as a diameter derived based on the volume of a bubble assuming a spherical shape.

[0029] The method for producing the microbubble water is not particularly limited, and examples thereof include an ejector method, a cavitation method, a swirling flow method, and a pressurized dissolution method. Examples of the ejector method include a method in which a pressurized liquid is sent to an ejector, and the gas self-absorbed by countless separation flows generated inside the ejector is atomized to generate bubbles. Examples of the cavitation method include a method in which a pressurized liquid is sent to a generator having a cavitation structure, and the dissolved gas contained in the liquid is precipitated by utilizing the cavitation phenomenon (cavitation phenomenon) generated in the structure to generate bubbles. Examples of the swirling flow method include a method in which a pressurized liquid is sent from an eccentric direction to a generator having a cylindrical structure, and the air is self-absorbed by an air column formed in the center of the cylinder, and bubbles are generated by the shear force generated by the speed difference when the liquid is discharged. Examples of the pressurized dissolution method include a method in which gas is forcibly dissolved under pressure, and bubbles are precipitated by decompression (opening to the atmosphere). As a microbubble generating device, a swirling type microbubble generating device that is not easily affected by water quality is preferable. Specifically, a microbubble generator using a YJ nozzle manufactured by By-Clean Co., Ltd. is preferred. The microbubble water is preferably microbubble water produced by a microbubble generator using a YJ nozzle manufactured by By-Clean Co., Ltd.

[0030] The iron oxide is not particularly limited, but examples thereof include iron oxide generated by immersing an iron-containing material in microbubble water as described above (iron oxide formed by oxidizing the iron of the iron-containing material).

[0031] The concentration of the iron oxide in the first treatment agent is preferably 0.01 to 50% by mass, more preferably 0.1 to 20% by mass, and even more preferably 0.1 to 10% by mass, relative to the first treatment agent. If the concentration of the iron oxide is too low, the quality of the finally obtained recycled fine aggregate for concrete tends not to be sufficiently improved. This is considered to be because the cement component attached to the fine aggregate is not sufficiently swollen by the first treatment agent, and the cement component is difficult to be suitably removed from the fine aggregate even when the second treatment agent is added. Also, if the concentration of the iron oxide is too high, not only the effect of improving the quality of the finally obtained recycled fine aggregate for concrete is saturated, but also the influence of the iron oxide that may affect the quality of the finally obtained recycled fine aggregate for concrete may become large. Therefore, if the concentration of the iron oxide is within the above range, a high-quality recycled fine aggregate for concrete can be suitably obtained.

[0032] The second addition step includes adding a second treatment agent containing a cationic surfactant to the derived material to which the first treatment agent has been added.

[0033] The second treatment agent is not particularly limited as long as it is a treatment agent containing a cationic surfactant, and examples thereof include an aqueous solution in which a cationic surfactant is dissolved in water. In addition, when the second treatment agent contains water, for example, when the second treatment agent is an aqueous solution in which a cationic surfactant is dissolved in water, the water may be general water such as tap water and industrial water, or may be microbubble water. In addition, as long as the second treatment agent contains a cationic surfactant, it may contain components other than the cationic surfactant.

[0034] The cationic surfactant is not particularly limited, and examples thereof include quaternary ammonium surfactants and amine surfactants. More specific examples thereof include amine salts (alkylamine salts, amide-bonded amine salts, ester-bonded amine salts, etc.), quaternary ammonium salts (alkylammonium salts, amide-bonded ammonium salts, ester-bonded ammonium salts, ether-bonded ammonium salts, etc.), pyridinium salts (alkylpyridinium salts, amide-bonded pyridinium salts, ether-bonded pyridinium salts, ester-bonded pyridinium salts, etc.), and the like.

[0035] Examples of the quaternary ammonium surfactant include tetraalkyl ammonium hydroxide, alkyl trimethyl ammonium chloride, dialkyl dimethyl ammonium chloride, tetraalkyl ammonium chloride, and alkyl benzyl dimethyl ammonium chloride. Examples of the tetraalkyl ammonium hydroxide include tetraethyl ammonium hydroxide (TEAH) and tetrabutyl ammonium hydroxide (TBAH). Examples of the alkyl trimethyl ammonium chloride include lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, and cetyl trimethyl ammonium chloride. Examples of the dialkyl dimethyl ammonium chloride include dilauryl dimethyl ammonium chloride and distearyl dimethyl ammonium chloride. Examples of the tetraalkyl ammonium chloride include tetraethyl ammonium chloride and tetrabutyl ammonium chloride.

[0036] Examples of the amine surfactant include ethylamine chloride, diethylamine chloride, triethylamine chloride, butylamine chloride, dibutylamine chloride, tributylamine chloride, octylamine chloride, dioctylamine chloride, trioctylamine chloride, dodecylamine chloride, didodecylamine chloride, tridodecylamine chloride, stearylamine chloride, and distearylamine chloride.

[0037] The cationic surfactants may be used alone or in combination of two or more kinds.

[0038] The concentration of the cationic surfactant in the second treatment agent is preferably 0.01 to 20% by mass, more preferably 0.1 to 15% by mass, and even more preferably 0.1 to 10% by mass, based on the second treatment agent. If the concentration of the cationic surfactant is too low, the quality of the finally obtained recycled fine aggregate for concrete tends not to be sufficiently improved. This is considered to be because the cement content is difficult to be suitably removed from the fine aggregate even if the second treatment agent is added. Also, if the concentration of the cationic surfactant is too high, not only the effect of improving the quality of the finally obtained recycled fine aggregate for concrete is saturated, but also the cationic surfactant may remain in the finally obtained recycled fine aggregate for concrete, and the influence of the cationic surfactant that may affect the quality of the finally obtained recycled fine aggregate for concrete may become large. Therefore, if the concentration of the cationic surfactant is within the above range, a high-quality recycled fine aggregate for concrete can be suitably obtained.

[0039] The manufacturing method may include a step (third adding step) of adding a third treating agent containing percarbonate to the derived material to which the second treating agent has been added. By including the third adding step, the manufacturing method can obtain a higher quality recycled fine aggregate for concrete. This is believed to be because the cement content is more suitably removed from the fine aggregate contained in the derived material to be used as fine aggregate for concrete by the third treating agent. The third adding step is not particularly limited as long as it is a step of adding the third treating agent to the derived material to which the second treating agent has been added.

[0040] The third treatment agent is not particularly limited as long as it is a treatment agent containing percarbonate, and examples thereof include an aqueous solution in which percarbonate is dissolved in water. In addition, when the third treatment agent contains water, for example, when the third treatment agent is an aqueous solution in which percarbonate is dissolved in water, the water may be general water such as tap water and industrial water, or may be microbubble water. In addition, as long as the third treatment agent contains percarbonate, it may contain components other than percarbonate. Examples of components other than percarbonate contained in the third treatment agent include a pH adjuster.

[0041] The percarbonate is not particularly limited, but examples thereof include sodium percarbonate, potassium percarbonate, calcium percarbonate, magnesium percarbonate, and ammonium percarbonate. Among these, sodium percarbonate is preferred. The percarbonate may be used alone or in combination of two or more.

[0042] The concentration of the percarbonate in the third treatment agent is preferably 0.01 to 20% by mass, more preferably 0.1 to 15% by mass, and even more preferably 0.1 to 10% by mass, relative to the third treatment agent. If the concentration of the percarbonate is too low, the effect of adding the third treatment agent, for example, the effect of removing the cement from the fine aggregate contained in the derived material that becomes the fine aggregate for concrete, tends not to be fully exhibited. Therefore, even if the third treatment agent is added, the quality of the finally obtained recycled fine aggregate for concrete tends not to be sufficiently improved. In addition, if the concentration of the percarbonate is too high, not only the effect of improving the quality of the finally obtained recycled fine aggregate for concrete is saturated, but also the influence of the percarbonate that may affect the quality of the finally obtained recycled fine aggregate for concrete may be large, such as the percarbonate remaining in the finally obtained recycled fine aggregate for concrete. Therefore, if the concentration of the percarbonate is within the above range, a higher quality recycled fine aggregate for concrete can be preferably obtained.

[0043] The manufacturing method may include a step of spraying microbubble water onto the derived material to which the second treatment agent has been added, or a step of spraying microbubble water onto the derived material to which the third treatment agent has been added, or a step of immersing the derived material to which the second treatment agent has been added in microbubble water, or a step of immersing the derived material to which the third treatment agent has been added in microbubble water (a microbubble water treatment step). By including the microbubble water treatment step, the manufacturing method can obtain a higher quality recycled fine aggregate for concrete. This is considered to be due to the following. It is considered that the cement content can be more suitably removed from the fine aggregate contained in the derived material to be used as fine aggregate for concrete by spraying the microbubble water or immersing the derived material in the microbubble water. The cationic surfactant contained in the second treatment agent may remain in the fine aggregate. In addition, when the third treatment agent is added, the percarbonate contained in the third treatment agent may remain. It is believed that by spraying the fine aggregate with the microbubble water or immersing the fine aggregate in the microbubble water, the cationic surfactant and the percarbonate that may remain in the fine aggregate can be more effectively removed from the fine aggregate, and therefore it is believed that a higher quality recycled fine aggregate for concrete can be obtained.

[0044] In this manufacturing method, the addition of the first treatment agent, the second treatment agent, the third treatment agent, and the microbubble water in the microbubble water treatment step to the derived material and the derived material to which any of the treatment agents has been added is not particularly limited as long as the added treatment agent comes into contact with the derived material. Examples of the method of adding to the derived material include a method of pouring, a method of immersing, and a method of pouring. Examples of the method of pouring include a method of spraying, a method of spreading (scattering), and the like.

[0045] After the addition, the added derived material may be stirred. The stirring time is not particularly limited as long as the derived material is sufficiently mixed, and is preferably 30 seconds to 24 hours, and more preferably 5 minutes to 15 hours. The amounts of the first treatment agent, the second treatment agent, the third treatment agent, and the microbubble water in the microbubble water treatment step added are not particularly limited as long as the derived material can be sufficiently contacted. In the case of such addition, the amount added is preferably 0.1 to 1000 parts by mass, and more preferably 1 to 500 parts by mass, relative to 100 parts by mass of the derived material. If the amount added is too small, the quality of the finally obtained recycled fine aggregate for concrete tends not to be sufficiently improved. This is considered to be because the cement component attached to the fine aggregate is not sufficiently swollen, and the cement component is difficult to be suitably removed from the fine aggregate. If the amount added is too large, not only the effect of improving the quality of the finally obtained recycled fine aggregate for concrete is saturated, but also the effect of removing the cement component thereafter may be difficult to be fully exhibited. Therefore, when the amount of addition is within the above range, a high-quality recycled fine aggregate for concrete can be suitably obtained.

[0046] In the case of immersion, the immersion time is not particularly limited as long as the derived product can be sufficiently contacted with the treatment agent, and is preferably, for example, 30 seconds to 24 hours, and more preferably, 5 minutes to 15 hours. The temperature of the treatment agent in which the derived product is immersed is not particularly limited, and is preferably, for example, 0 to 50°C, and more preferably, 5 to 35°C, and may be, for example, room temperature.

[0047] When spraying the derived material, the spraying time is not particularly limited as long as the treatment agent can be sufficiently in contact with the derived material, and is preferably 30 seconds to 24 hours, and more preferably 5 minutes to 2 hours. When sprinkling (dispersing) the derived material, the number of sprays is not particularly limited as long as the treatment agent can be sufficiently in contact with the derived material, and is preferably 2 times or more, more preferably 2 to 5 times, and even more preferably 2 to 4 times. The spraying may be performed using, for example, a spiral water washer, a spiral cleaning machine, a spiral classifier, or the like. When such a treatment agent is sprayed on the derived material, the temperature of the treatment agent is not particularly limited, and is preferably 0 to 50°C, and more preferably 5 to 35°C, and may be, for example, room temperature.

[0048] The amount of the treatment agent added in the addition step is not particularly limited in the case of the immersion and spraying, so long as the treatment agent can be sufficiently brought into contact with the derived material. The amount of the treatment agent added is, for example, preferably 0.05 to 30% by volume, more preferably 1 to 20% by volume, and even more preferably 3 to 10% by volume, relative to the derived material. The amount added is particularly suitable when the addition step is carried out on a batch scale, such as by immersing the derived material in the treatment agent. In addition, the amount of the treatment agent added is, for example, 0.05 to 30% by volume, relative to the derived material, more preferably 1 to 20% by volume, and even more preferably 3 to 10% by volume. 3The amount is preferably 1 to 300 kg, more preferably 5 to 100 kg, relative to the amount of the recovered fine aggregate. The amount of the added agent is particularly suitable when the adding step is performed as a continuous step, such as by applying the treating agent to the derived material. If the amount of the added agent is too small, the quality of the finally obtained recycled fine aggregate for concrete tends not to be sufficiently improved. This is considered to be because the cement content attached to the fine aggregate is not sufficiently swollen by the treating agent, and the cement content is difficult to be suitably removed from the derived material even if the treating agent is added. Also, if the amount of the added agent is too large, not only is the effect of improving the quality of the finally obtained recycled fine aggregate for concrete saturated, but the effect of removing the cement content by the treating agent added thereafter may be difficult to be fully exerted. Therefore, if the amount of the added agent is within the above range, a high-quality recycled fine aggregate for concrete can be suitably obtained.

[0049] When the derived material is returned ready-mixed concrete or remaining ready-mixed concrete, the manufacturing method may include a step (extraction step) of extracting fine aggregate (solid content of a size that can become fine aggregate) from the derived material. The extraction step may include a method of settling solid content in the returned ready-mixed concrete or remaining ready-mixed concrete to which the first and second treatment agents have been added, and sieving the solid content obtained by this settling to separate fine aggregate (solid content of a size that can become fine aggregate). In addition, the first treatment agent, the second treatment agent, and the third treatment agent may be removed from the extracted fine aggregate using a spiral water washer, a spiral cleaning machine, a spiral screw type sand recovery machine, a spiral classifier, or the like. The fine aggregate extracted in this manner is obtained as recovered fine aggregate for concrete. In addition, in the manufacturing method, when the derived material is a fine aggregate extracted from the returned ready concrete or the residual ready concrete, water such as microbubble water may be added to the returned ready concrete, and the extracted material may be the returned ready concrete to which the water has been added, in the extracting step. By doing so, the fine aggregate extracted from the returned ready concrete or the residual ready concrete can be used as the derived material.

[0050] The manufacturing method may include a step of removing magnetic body components from the obtained recycled fine aggregate for concrete by magnetic force (removal step). In the removal step, for example, magnetic body components such as iron oxide contained in the first treatment agent are removed from the fine aggregate for concrete by magnetic force. The removal is not particularly limited, and can be performed using a magnetic separator or the like. Examples of the magnetic separator include a drum-type magnetic separator using a permanent magnet, a belt-type magnetic separator using a permanent magnet, a drum-type magnetic separator using an electromagnet, and a belt-type magnetic separator using an electromagnet. Examples of the magnetic separator include a suspended electromagnet for removing iron. The magnetic body components removed in the removal step are not particularly limited as long as they are components that should not be contained in the recycled fine aggregate for concrete, and examples of the magnetic body components include iron oxide contained in the first treatment agent.

[0051] As described above, the manufacturing method of recycled fine aggregate for concrete can manufacture high-quality recycled fine aggregate for concrete. The manufacturing method of recycled fine aggregate for concrete can manufacture fine aggregate for concrete of higher quality than recycled aggregate specified in, for example, JIS A 5308:2019. In addition, the manufacturing method of recycled fine aggregate for concrete can manufacture recycled fine aggregate for concrete of higher quality than recycled aggregate for concrete H specified in JIS A 5021:2018 and recycled aggregate for concrete M specified in JIS A 5022:2018.

[0052] The recycled fine aggregate for concrete obtained by the method for producing recycled fine aggregate for concrete has, for example, an oven-dry density of 1.5 g / cm 3 The recycled fine aggregate for concrete has a density of 1.5 g / cm3 or more, a water absorption rate of 7% or less, and a color tone expressed by the Lab system with an a value of 0 to 3 and a b value of 5 to 15. Such recycled fine aggregate for concrete is a high-quality recycled fine aggregate for concrete. In addition, fine aggregates other than recycled fine aggregates (normal fine aggregates) have an oven-dry density of 1.5 g / cm3 or more, a water absorption rate of 7% or less, and a color tone expressed by the Lab system with an a value of 0 to 3 and a b value of 5 to 15. 3 It is possible to obtain fine aggregate having a water absorption rate of 7% or less and a color tone expressed by the Lab system with an a value of 0 to 3 and a b value of 5 to 15. However, it has not been possible to produce such a recycled fine aggregate for concrete from recycled fine aggregate in the past. The method for producing recycled fine aggregate for concrete according to this embodiment provides the recycled fine aggregate for concrete.

[0053] The bone dry density of the recycled fine aggregate for concrete is 1.5 g / cm3 as described above. 3 More than 2g / cm 3 It is preferable that the content is 2.5 g / cm or more. 3 The bone dry density of the recycled fine aggregate for concrete is preferably 4.5 g / cm or more. 3 If the bone dry density is within the above range, it is understood that there are few voids, and therefore it is considered that the cement content in the derived material is sufficiently removed.3 ) is the mass (g) of a substance in a dry state divided by its volume (cm 3 ) The bone-dry state is the state in which a sample is left in a hot air dryer at 110°C and the mass of the sample is measured at 15-minute intervals, with the difference in mass before and after being within 0.1% of the mass after. The bone-dry state mass is the mass of the sample when it has reached a bone-dry state. The bone-dry state volume is the volume of the sample when it has reached a bone-dry state.

[0054] The water absorption rate of the recycled fine aggregate for concrete is 7% or less, preferably 5% or less, more preferably 4.5% or less, even more preferably 4% or less, particularly preferably 3.5% or less, and particularly more preferably 3% or less. The water absorption rate of the recycled fine aggregate for concrete is preferably as low as possible, but in practice, the limit is often about 0.5%, and the lower limit of the water absorption rate range of the recycled fine aggregate for concrete is, for example, 0.5%. If the water absorption rate is within the above range, it is considered that the cement content in the derived material has been sufficiently removed, and the recycled fine aggregate for concrete is of high quality. The water absorption rate is the percentage of the total amount of water contained in the aggregate in a surface dry water-saturated state relative to the mass of the aggregate in an absolute dry state. In other words, it is a numerical value that represents the amount of water that the aggregate can contain as a percentage. The surface dry water-saturated state (surface dry state) is a state in which there is no surface water on the aggregate and all the voids inside the aggregate grains are filled with water. The total amount of water contained in surface-dry, water-saturated aggregate is the difference between the mass of the surface-dry aggregate and the mass of the bone-dry aggregate.

[0055] When the color tone of the recycled fine aggregate for concrete is expressed by the Lab system, the a-value is 0 to 3, preferably 0.5 to 3, and more preferably 0.5 to 2.5, and the b-value is 5 to 15, preferably 7 to 15, and more preferably 7 to 12. Although the a-value and b-value may be within the above ranges in the case of conventional fine aggregate for concrete (fine aggregate that is not recycled fine aggregate), it has been difficult to achieve the a-value and b-value within the above ranges in the case of recycled fine aggregate for concrete.

[0056] The angle of repose of the recycled fine aggregate for concrete is preferably 45° or less, more preferably 42° or less, even more preferably 40° or less, and particularly preferably 38° or less. The smaller the angle of repose of the fine aggregate, the better, but in practice, the limit is often about 10°, and the lower limit of the range of the angle of repose of the recycled fine aggregate for concrete is, for example, 10°. If the angle of repose is within the above range, the adhesiveness between the fine aggregates is reduced because the cement paste has been removed. This reduces the adhesion between the fine aggregates, improving storage stability.

[0057] The fine powder content of the recycled fine aggregate for concrete is preferably 7% or less, more preferably 5% or less, and even more preferably 3% or less. The fine powder content is the ratio of fine powder contained in the aggregate that passes through a 75 μm (0.075 mm) mesh sieve to the total mass of the aggregate. If the fine powder content is within the above range, the adhesiveness between the fine aggregates is reduced because the cement paste has been removed. This reduces the adhesion between the fine aggregates, improving storage stability.

[0058] The Ca content in the entire recycled fine aggregate for concrete is preferably 25% by mass or less, and more preferably 5 to 20% by mass. The Si content in the entire recycled fine aggregate for concrete is preferably 70% by mass or more, and more preferably 70 to 95% by mass. Furthermore, the ratio of the Ca content to the Si content (Ca content / Si content) in the entire recycled fine aggregate for concrete is preferably 0 to 0.5, and more preferably 0 to 0.4. The Si content and Ca content in the entire recycled fine aggregate for concrete can be measured, for example, by fluorescent X-ray analysis. Furthermore, the ratio of the Ca content to the Si content (Ca content / Si content) in the entire recycled fine aggregate for concrete can be calculated from these Si content and Ca content.

[0059] The amount of Ca on the surface of the recycled fine aggregate for concrete is preferably 9% by mass or less, and more preferably 0.5 to 7% by mass. The amount of Si on the surface of the recycled fine aggregate for concrete is preferably 12 to 40% by mass, and more preferably 15 to 30% by mass. The ratio of the amount of Ca to the amount of Si on the surface of the recycled fine aggregate for concrete (Ca amount / Si amount) is preferably 0.22 or less, and more preferably 0.05 to 0.2. The amount of Si and the amount of Ca on the surface of the recycled fine aggregate for concrete can be measured, for example, by X-ray analysis, and more specifically, can be measured by an energy dispersive X-ray analyzer (EDS) provided in a scanning electron microscope. From these amounts of Si and Ca, the ratio of the amount of Ca to the amount of Si in the entire recycled fine aggregate for concrete (Ca amount / Si amount) can be calculated.

[0060] [Method of manufacturing ready-mix concrete] A method for producing ready-mixed concrete according to another embodiment of the present invention includes a step (mixing step) of mixing cement, aggregate, and water, and uses aggregate including the recycled fine aggregate for concrete (recycled fine aggregate for concrete produced by the method for producing recycled fine aggregate for concrete) as the aggregate. Specific examples of the method for producing ready-mixed concrete include a method similar to a method for producing general ready-mixed concrete, except that the recycled fine aggregate for concrete is used as the aggregate. By using the recycled fine aggregate for concrete as the aggregate, excellent ready-mixed concrete can be produced. By including the recycled fine aggregate for concrete in the ready-mixed concrete, excellent ready-mixed concrete can be obtained. In addition, the ready-mixed concrete may include only the recycled fine aggregate for concrete as a fine aggregate, or may include the recycled fine aggregate for concrete and other fine aggregates. In addition, the ready-mixed concrete may include coarse aggregate. In the mixing step in the method for producing ready-mixed concrete, in addition to cement, aggregate, and water, for example, other components may also be mixed as necessary. The mixing step is a step of mixing cement, aggregate, water, and, as necessary, the other components, etc. The mixing step is not particularly limited except that the recycled aggregate for concrete is used as the aggregate, and examples of the mixing step include a mixing step in a general method for producing ready-mix concrete.

[0061] The cement is not particularly limited as long as it is a cement used in producing ready-mixed concrete. Specifically, portland cement such as ordinary portland cement, early-strength portland cement, ultra-early-strength portland cement, moderate-heat portland cement, low-heat portland cement, and white portland cement, blast-furnace cement, alumina cement, silica cement, and silica fume cement can be mentioned. Among these, portland cement is preferable, and ordinary portland cement is more preferable. In addition, examples of ordinary portland cement include those described in JIS R 5210:2009. It is considered that the use of such cement can more suitably proceed the hydration reaction and the porazon reaction of the cement. Therefore, by using such cement, ready-mixed concrete that can obtain a concrete structure having higher strength and higher stability can be obtained. The content of the cement is preferably 8.84 to 18.13% by volume with respect to the ready-mixed concrete. If the amount of the cement is too small, the strength of the obtained concrete structure tends to be insufficient. In addition, if the amount of the cement is too large, the stability of the obtained concrete structure tends to be insufficient. This is believed to be because if the amount of cement is too large, the amount of coal ash becomes relatively small, making it difficult for the pozzolanic reaction to proceed favorably, and the effect of improving stability due to the pozzolanic reaction becomes insufficient.

[0062] The aggregate is not particularly limited as long as it contains the recycled fine aggregate for concrete as described above, and may contain aggregate other than the recycled fine aggregate for concrete. Examples of the aggregate include fine aggregate and coarse aggregate. As described above, the ready-mix concrete may contain the recycled fine aggregate for concrete alone as the fine aggregate, or may use the recycled fine aggregate for concrete in combination with other fine aggregates. Even when the recycled fine aggregate for concrete is used alone as the fine aggregate for the ready-mix concrete, aggregate other than the recycled fine aggregate for concrete may be used as the coarse aggregate. The aggregate other than the recycled fine aggregate for concrete is not particularly limited as long as it is an aggregate that is generally used when producing ready-mix concrete. The fine aggregate other than the recycled fine aggregate for concrete is not particularly limited as long as it is a fine aggregate to be contained in the ready-mix concrete. Examples of the fine aggregate include natural sand such as silica sand, and crushed stone powder. Examples of fine aggregates other than the recycled fine aggregate for concrete include sand and the like specified in JIS A 5005:2020. The coarse aggregate is not particularly limited as long as it is a fine aggregate to be contained in the fresh concrete. Examples of the coarse aggregate include crushed stone and the like. Examples of the coarse aggregate include coarse aggregate 1505 and coarse aggregate 2010 specified in JIS A 5005:2020, and mixtures thereof. Examples of aggregates other than the recycled fine aggregate for concrete include mountain sand, which is a sandy soil that is collected as a construction material from alluvial deposits in land areas such as mountains, hills, and plateaus. The content of the aggregate is preferably 66.80 to 90.33% by volume with respect to the fresh concrete. Among the aggregates, the content of the recycled fine aggregate for concrete is preferably 31.31 to 43.10% by volume with respect to the fresh concrete.

[0063] The water is not particularly limited as long as it is water that is generally used when producing ready-mix concrete. Examples of the water include general water such as tap water and industrial water. The content of the water is preferably 6.84 to 8.85% by volume relative to the ready-mix concrete.

[0064] The ready-mix concrete may contain, in addition to the cement, the aggregate, and water, other components that are generally added to ready-mix concrete, etc. Examples of the other components include coal ash, slag powder, surfactants such as air entraining agents (AE agents), and admixtures such as AE water reducing agents.

[0065] The coal ash is not particularly limited as long as it is ash generated when coal is burned. Examples of the coal ash include fly ash and clinker ash, and fly ash is preferably used.

[0066] The slag powder is not particularly limited, and examples thereof include blast furnace slag powder, copper slag powder, etc. That is, the slag powder is preferably blast furnace slag powder, copper slag powder, or a mixture of blast furnace slag powder and copper slag powder.

[0067] The admixture is not particularly limited as long as it is an admixture to be contained in ready-mix concrete. Examples of the admixture include surfactants such as air entraining agents and AE water-reducing agents, and specifically, water-reducing agents (high-performance AE water-reducing agents) specified in JIS A 6204:2011.

[0068] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these. EXAMPLES

[0069] First, each of the treating agents used in this embodiment will be described.

[0070] [First treatment agent] (First treatment agent A) 1 kg of iron nails was immersed in 10 kg of microbubble water produced using a swirl type microbubble water generator (a microbubble water generator using a YJ nozzle manufactured by By Clean Co., Ltd.), and the microbubble water in which the iron nails were immersed was bubbled for 12 hours using the microbubble generator. By doing so, the microbubble water turned black-brown. A black-brown component was dispersed in the microbubble water that turned black-brown, and as a result of analyzing the black-brown component by microscopic Raman spectroscopy, it was found to be iron oxide (magnetite: Fe3O4). From this, it was found that this liquid was microbubble water in which iron oxide generated by the oxidation of the iron nails was dispersed. This microbubble water in which iron oxide generated by the oxidation of the iron nails was dispersed was used as a first treatment agent A containing microbubble water and iron oxide. The concentration of iron oxide in this first treatment agent A was 3 mass% relative to the first treatment agent A.

[0071] (First treatment agent B) 1 kg of iron from a used disposable warmer was immersed in 10 kg of microbubble water produced using a swirl-type microbubble water generator (a microbubble water generator using a YJ nozzle manufactured by By Clean Co., Ltd.), and the microbubble water in which the iron-containing material from the used disposable warmer was immersed was bubbled for 12 hours using the microbubble generator. By doing so, the microbubble water turned blackish brown. A blackish brown component was dispersed in the microbubble water that turned blackish brown, and as a result of analyzing this blackish brown component by microscopic Raman spectroscopy, it was found to be iron oxide (magnetite: Fe3O4). From this, it was found that this liquid was microbubble water in which iron oxide generated by the oxidation of iron contained in the iron-containing material in the used disposable warmer was dispersed. The microbubble water in which iron oxide generated by the oxidation of iron contained in the iron-containing material in the used disposable warmer was dispersed was used as the first treatment agent B containing microbubble water and iron oxide. The concentration of iron oxide in this first treatment agent B was 4 mass % relative to the first treatment agent B.

[0072] [Second treatment agent] A 1% by mass aqueous solution of a cationic surfactant (quaternary ammonium salt type cationic surfactant) (lauryltrimethylammonium chloride, Kotamin 24P manufactured by Kao Corporation) was used as the second treatment agent containing a cationic surfactant.

[0073] [Third treatment agent] A solution in which sodium percarbonate (manufactured by Hayashi Pure Chemical Industries, Ltd.) was dissolved in the microbubble water (microbubble water produced using a swirl-type microbubble water generator) was used as a third treatment agent containing percarbonate. The concentration of sodium percarbonate (percarbonate) in this third treatment agent was 10% by mass relative to the third treatment agent.

[0074] [Example 1] 1 kg of the first treatment agent A (first treatment agent derived from iron nails) was added to 1 kg of returned ready-mixed concrete, and the mixture was stirred for 10 hours. Then, 0.1 kg of the second treatment agent was added to the returned ready-mixed concrete to which the first treatment agent A was added, and the mixture was stirred for 5 hours. Then, the solid content was allowed to settle in the returned ready-mixed concrete to which the first treatment agent A and the second treatment agent were added, and the solid content obtained by this settling was sieved to separate the fine aggregate from the solid content. The fine aggregate obtained by this separation was washed with water using a spiral screw type sand recovery machine (manufactured by Kitagawa Iron Works Co., Ltd.), dried, and then stored. The fine aggregate obtained in this manner was obtained as the recovered fine aggregate for concrete according to Example 1.

[0075] [Example 2] 10 kg of the microbubble water (microbubble water produced using a swirling type microbubble water generator) was added to 1 kg of the returned ready-mixed concrete and stirred. The solids in the returned ready-mixed concrete to which the microbubble water was added were allowed to settle, and the solids obtained by this settling were sieved to separate the fine aggregate from the solids. The fine aggregate obtained by this separation was dispersed in the microbubble water and washed. 1 kg of the first treatment agent B (a first treatment agent derived from a used disposable warmer) was added to this fine aggregate, and the mixture was stirred for 10 hours. Then, 0.5 kg of the second treatment agent was added to the fine aggregate to which the first treatment agent B was added, and the mixture was stirred for 8 hours. Then, 1 kg of the third treatment agent was added to the fine aggregate to which the first treatment agent B and the second treatment agent were added. The fine aggregate to which the third treatment agent was added was stirred for 1 hour, and then the fine aggregate was separated using the spiral water washer. The fine aggregate obtained by this separation was washed with water using the spiral water washer, dried, and then stored. The fine aggregate thus obtained was obtained as the recycled fine aggregate for concrete according to Example 2.

[0076] [Example 3] 10 kg of the microbubble water (microbubble water produced using a swirling type microbubble water generator) was added to 1 kg of returned ready-mixed concrete and stirred. The solids in the returned ready-mixed concrete to which the microbubble water was added were allowed to settle, and the solids obtained by this settling were sieved to separate the fine aggregate from the solids. The fine aggregate obtained by this separation was dispersed in the microbubble water and washed. 2 kg of the first treatment agent A (first treatment agent derived from iron nails) was added to this fine aggregate and stirred for 10 hours, and then 0.1 kg of the second treatment agent was added to the fine aggregate to which the first treatment agent A was added and stirred for 5 hours. Thereafter, the fine aggregate to which the first treatment agent A and the second treatment agent were added was stirred for 10 hours, and then the fine aggregate was separated using the spiral water washer. The fine aggregate obtained by this separation was washed with water using the spiral water washer, dried, and then stored. The fine aggregate obtained in this manner was obtained as the recovered fine aggregate for concrete according to Example 3.

[0077] [Comparative Example 1] 10 kg of the microbubble water (microbubble water produced using a swirl type microbubble water generator) was added to 1 kg of returned ready mixed concrete and stirred. The solids in the returned ready mixed concrete to which the microbubble water was added were allowed to settle, and the solids obtained by this settling were sieved to separate the fine aggregate from the solids. The fine aggregate obtained by this separation was washed with water using the spiral water washer, dried, and then stored. The fine aggregate thus obtained was obtained as the recovered fine aggregate for concrete according to Comparative Example 1. Comparative Example 1 is an example in which the first treatment agent and the second treatment agent were not used.

[0078] [Comparative Example 2] 10 kg of the microbubble water (microbubble water produced using a swirling type microbubble water generator) was added to 1 kg of returned ready-mixed concrete and stirred. The solids in the returned ready-mixed concrete to which the microbubble water was added were allowed to settle, and the solids obtained by this settling were sieved to separate fine aggregate from the solids. The fine aggregate obtained by this separation was dispersed in the microbubble water and washed. 1 kg of the first treatment agent A (first treatment agent derived from iron nails) was added to this fine aggregate, and the mixture was stirred for 10 hours. Thereafter, the fine aggregate to which the microbubble water was added was stirred for 12 hours, and then the fine aggregate was separated using the spiral water washer. The fine aggregate obtained by this separation was washed with water using the spiral water washer, dried, and then stored. The fine aggregate obtained in this manner was obtained as a recycled fine aggregate for concrete according to Comparative Example 2. Comparative Example 2 is an example in which the second treatment agent is not used.

[0079] [Comparative Example 3] 10 kg of the microbubble water (microbubble water produced using a swirling type microbubble water generator) was added to 1 kg of returned ready-mixed concrete and stirred. The solids in the returned ready-mixed concrete to which the microbubble water was added were allowed to settle, and the solids obtained by this settling were sieved to separate fine aggregate from the solids. The fine aggregate obtained by this separation was dispersed in the microbubble water and washed. 1 kg of the second treatment agent was added to this fine aggregate, and the mixture was stirred for 5 hours. The fine aggregate to which the second treatment agent was added was stirred for 12 hours, and then the fine aggregate was separated using the spiral water washer. The fine aggregate obtained by this separation was washed with water using the spiral water washer, dried, and then stored. The fine aggregate obtained in this manner was obtained as a recycled fine aggregate for concrete according to Comparative Example 3. Comparative Example 3 is an example in which the first treatment agent was not used.

[0080] [Comparative Example 4] 2m 3 The returned fresh concrete was loaded into a double twin-shaft high-intensity mixer. After the returned fresh concrete was loaded into the mixer, 2 kg of an anionic polyacrylamide organic powder flocculant mixture was added and mixed for 1 minute and 30 seconds. After mixing, the coarse material was discharged and separated in a vibrating sieve with 5 mm openings. Thus, the fine aggregate passed through the 5 mm sieve and was collected at the bottom. The fine aggregate collected at the bottom was dried and then stored. The fine aggregate thus obtained was obtained as the recovered fine aggregate for concrete according to Comparative Example 4.

[0081] The bone dry density, water absorption rate, angle of repose, and color values ​​(L value, a value, and b value) of the recycled fine aggregate for concrete produced as described above were measured by the following methods. The results are shown in Table 1 below.

[0082] (absolutely dry density) Each of the obtained recycled fine aggregates for concrete was left in a hot air dryer at a temperature of 110°C, and its mass was measured at 15-minute intervals. It was left in the hot air dryer until the difference in mass before and after the measurement was within 0.1% of the mass after the measurement (absolutely dry state). The mass (g) and volume (cm3) of the recycled fine aggregates for concrete in the absolute dry state were 3 ) and the mass (g) of the bone-dry recycled fine aggregate for concrete was calculated by multiplying the volume (cm 3 ) to obtain the bone dry density (g / cm 3 ) was calculated.

[0083] (Water absorption rate) The water absorption rate of each of the obtained recycled fine aggregates for concrete was measured by a method conforming to JIS A 1109:2020. Specifically, first, the recycled fine aggregate for concrete was placed in a state in which there was no surface water and all of the internal voids were filled with water (surface dry water-saturated state), and the mass (g) of the recycled fine aggregate for concrete in this surface dry water-saturated state was measured. Then, the difference between the mass (g) of the recycled fine aggregate for concrete in the surface dry water-saturated state and the mass (g) of the recycled fine aggregate for concrete in the bone dry state was calculated to obtain the total amount of water (g) contained in the recycled fine aggregate for concrete in the surface dry water-saturated state. Then, the water absorption rate (%) was calculated by dividing the total amount of water (g) contained in the recycled fine aggregate for concrete in this surface dry water-saturated state by the mass (g) of the recycled fine aggregate for concrete in the bone dry state. That is, the water absorption rate (%) was obtained by calculating [(mass (g) of recovered fine aggregate for concrete in a surface-dry water-saturated state - mass (g) of recovered fine aggregate for concrete in an absolute dry state) / mass (g) of recovered fine aggregate for concrete in an absolute dry state × 100].

[0084] (Angle of repose) The angle of repose (°) of each of the obtained recycled fine aggregates for concrete was measured by a method in accordance with JIS R 9301-2-2:1999 Alumina powder - Part 2: Physical property measurement method -2.

[0085] (L value, a value, and b value) Each of the obtained recycled fine aggregates for concrete was placed in a 3 cm petri dish, and the L value, a value, and b value of the recycled fine aggregate for concrete in this state were measured using a spectrophotometer (CM-700 manufactured by Konica Minolta, Inc.).

[0086] (Si content, Ca content, and Ca content / Si content) The Si content (mass%) and Ca content (mass%) in the entire recovered fine aggregate for concrete were measured using a fluorescent X-ray analyzer (SEA6000VX HSFinder manufactured by Hitachi High-Tech Science Corp.) From the obtained Si content and Ca content, the ratio of the Ca content to the Si content (Ca content / Si content) in the entire recovered fine aggregate for concrete was calculated.

[0087] In addition, the Si content (mass%) and Ca content (mass%) on the surface of the recycled fine aggregate for concrete were measured using a scanning electron microscope (TM3030Plus manufactured by Hitachi High-Tech Technologies Corporation) equipped with an energy dispersive X-ray analyzer (EDS). From the obtained Si and Ca contents, the ratio of the Ca content to the Si content (Ca content / Si content) on the surface of the recycled fine aggregate for concrete was calculated.

[0088] [evaluation] The obtained recycled fine aggregate for concrete was evaluated by the following methods, and the results are shown in Table 1 below.

[0089] (External Observation) The appearance of the recycled fine aggregate for concrete was observed with a digital microscope manufactured by Sanwa Supply Co., Ltd. to observe the degree of adhesion of cement paste to the surface of the recycled fine aggregate for concrete. Specifically, the area where the cement paste was attached was visually determined from the image obtained by this observation, and the area was calculated. The results were evaluated according to the following criteria.

[0090] When the presence of cement paste could not be confirmed by visual inspection (i.e., when the area ratio of cement paste was 0%), it was evaluated as "1", when the area ratio of cement paste was more than 0% but not more than 20%, it was evaluated as "2", when the area ratio of cement paste was more than 20% but not more than 50%, it was evaluated as "3", when the area ratio of cement paste was more than 50% but not more than 80%, it was evaluated as "4", and when the area ratio of cement paste was more than 80%, it was evaluated as "5". It can be seen that the smaller the evaluation value, the more suitable the recycled fine aggregate for concrete that was obtained.

[0091] (Powder properties: cohesiveness) The recycled fine aggregate for concrete was stored at room temperature for one month. After this storage, the condition of the fine aggregate for concrete was visually observed. The results were evaluated according to the following criteria.

[0092] When no cohesion was observed, it was rated as "1", when only slight cohesion was observed, it was rated as "2", when cohesion was observed relatively throughout, it was rated as "3", when cohesion was observed relatively throughout and further when strong cohesion was partially observed, it was rated as "4", and when cohesion was observed relatively throughout, it was rated as "5". The smaller the rating number, the more suitable the recycled fine aggregate for concrete that was obtained.

[0093] Next, ready-mix concrete was produced using each of the obtained recycled fine aggregates for concrete. Specifically, ready-mix concrete was produced by mixing the following mixture composition (mass %).

[0094] The mixture was mixed to obtain 12.91% by mass of cement, 42.97% by mass of coarse aggregate, 35.86% by mass of recycled fine aggregate for concrete (recycled fine aggregate for concrete according to Examples 1 to 3 and Comparative Examples 1 to 4), 8.13% by mass of industrial water, and 0.13% by mass of admixture (Flolic SV-10, an AE water-reducing agent manufactured by Flolic Co., Ltd.). Ready-mix concrete was obtained in this manner.

[0095] Then, using each of the obtained ready mixed concretes, tests were conducted by a known method so as to achieve a nominal strength of 21 N and a target slump of 15 cm. The ready mixed concrete with the above mix was the standard mix for the above test. Specifically, the following evaluations were conducted. The results are shown in Table 1 below.

[0096] (Liquidity) The fluidity of the resulting ready mixed concrete was visually confirmed. The fluidity of ready mixed concrete is one of the indicators of workability on site, and if 9 to 10 workers on site judged the fluidity to be good, it was rated as "◎". If 6 to 8 workers on site judged the fluidity to be good, it was rated as "○". If 3 to 5 workers on site judged the fluidity to be good, it was rated as "△". If 0 to 2 workers on site judged the fluidity to be good, it was rated as "×".

[0097] (slump) The slump evaluation of the ready-mixed concrete was carried out in accordance with JIS A 1101:2020. Specifically, the height of the slump was measured immediately after the slump was formed as described above. In addition, the difference in the measured height from the target slump height of 15 cm (slump difference) was evaluated.

[0098] The evaluation of the slump height was carried out using ready mixed concrete immediately after production and ready mixed concrete 30 minutes after production.

[0099] (flow) The flow evaluation of the ready-mix concrete was performed in accordance with JIS A 1101:2020. Specifically, as described above, the spread of slump immediately after the slump was formed was evaluated as "standard," "large," or "small" according to the criteria in JIS A 1101:2020.

[0100] (Air volume) The air content of the ready-mixed concrete was measured by a method conforming to JIS A 1101:2020. The air content was then evaluated as "standard," "large," or "small" according to the standards of JIS A 1101:2020. Specifically, when the ratio of the volume of air mixed into the ready-mixed concrete to the volume of the ready-mixed concrete is 4 to 5% by volume, it is evaluated as "standard," when it exceeds 5% by volume, it is evaluated as "large," and when it is less than 4% by volume, it is evaluated as "small." In Comparative Example 1, the air content was 6.5% by volume.

[0101] (Mixed state) The mixed state of the obtained ready-mixed concrete was evaluated based on the viscosity of the ready-mixed concrete. For example, a good ready-mixed concrete is one that is soft but viscous. If 9 to 10 out of 10 workers on-site judged the mixed state of the ready-mixed concrete to be good, it was evaluated as "◎". If 6 to 8 out of 10 workers on-site judged the mixed state to be good, it was evaluated as "○". If 3 to 5 out of 10 workers on-site judged the mixed state to be good, it was evaluated as "△". If 0 to 2 out of 10 workers on-site judged the mixed state to be good, it was evaluated as "×".

[0102] As mentioned above, good ready-mix concrete is one that is soft but sticky. Therefore, the mixing state is more important in evaluating ready-mix concrete than the fluidity.

[0103] (strength) The strength of the concrete obtained by solidifying the resulting ready-mix concrete was measured according to a method in accordance with JIS A 1108:2018.The air content was then evaluated as "standard" or "poor" according to the criteria in JIS A 1108:2018.

[0104] (comprehensive evaluation) From the above evaluations, ready-mix concrete that could be judged to be very good was rated as "○", that which was inferior but could still be used was rated as "△", and that which was judged to be difficult to use as ready-mix concrete was rated as "×".

[0105] [Table 1]

[0106] It was found that by using recycled fine aggregate for concrete (Example 1) obtained by adding a first treatment agent containing microbubble water and iron oxide to returned ready-mix concrete or residual ready-mix concrete, and then adding a second treatment agent containing a cationic surfactant, a better ready-mix concrete was obtained than when the first treatment agent and the second treatment agent were not added (Comparative Example 1 and Comparative Example 4), when the second treatment agent was not added (Comparative Example 2), and when the first treatment agent was not added (Comparative Example 3). Furthermore, when using a recycled fine aggregate for concrete (Example 2) obtained by further adding a third treating agent containing percarbonate in addition to the first and second treating agents, microbubble water is added to returned ready mixed concrete or remaining ready mixed concrete, a first treating agent containing microbubble water and iron oxide is added to the fine aggregate extracted from the returned ready mixed concrete or remaining ready mixed concrete to which the microbubble water has been added, and then a second treating agent containing a cationic surfactant is added, it was found that using the recycled fine aggregate for concrete (Example 3) obtained by using the recycled fine aggregate for concrete of Example 1 can produce a better ready mixed concrete than when the recycled fine aggregate for concrete of Comparative Examples 1 to 4 is used.

Claims

1. A step of adding a first treatment agent containing microbubble water and iron oxide to a material derived from returned ready-mix concrete or residual ready-mix concrete; and adding a second treating agent containing a cationic surfactant to the derived material to which the first treating agent has been added.

2. The method for producing recycled fine aggregate for concrete according to claim 1 , further comprising the step of adding a third treating agent containing a percarbonate to the derived material to which the second treating agent has been added.

3. 2. The method for producing recycled fine aggregate for concrete according to claim 1, further comprising the step of spraying microbubble water onto the derived material to which the second treatment agent has been added, or the step of immersing the derived material to which the second treatment agent has been added in microbubble water.

4. 3. The method for producing recycled fine aggregate for concrete according to claim 2, further comprising the step of spraying microbubble water onto the derived material to which the third treatment agent has been added, or the step of immersing the derived material to which the third treatment agent has been added in microbubble water.

5. The method includes a step of mixing cement, aggregate, and water, A method for producing ready-mix concrete, using as the aggregate an aggregate containing recycled fine aggregate for concrete produced by the method for producing recycled fine aggregate for concrete according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Method for producing aggregate from returned concrete

    JP2020528858A

  • Water for producing concrete, method for producing water for producing concrete, and ready mixed concrete

    JP2022072175A

  • Manufacturing method of recycled fine aggregate for concrete, and manufacturing method of ready-mix concrete

    JP7407491B1

  • A carbonization apparatus of recycled aggregates using nano-bubble

    KR101740697B1

  • Recycled aggregate manufacturing method and recycled aggregate obtained from said method

    WO2013114526A1